A research guide to cartographic resources : print and electronic sources - Dodsworth, Eva H., 1976- (Rowman & Littlefield, 2018)
"The interdisciplinary uses of traditional cartographic resources and modern GIS tools allow for the analysis and discovery of information across a wide spectrum of fields. A Research Guide to Cartographic Resources navigates the numerous American and Canadian cartographic resources available in print, and online, offering researchers, academics and students with information on how to locate and access the large variety of resources, new and old. Dozens of different cartographic materials are highlighted and summarized, along with lists of map libraries and geospatial centers, and related professional associations. A Research Guide to Cartographic Resources consists of 18 chapters, two appendices, and a detailed index that includes place names, and libraries, structured in a manner consistent with most reference guides, including cartographic categories such as atlases, dictionaries, gazetteers, handbooks, maps, plans, GIS data and other related material. Almost all of the resources listed in this guide are categorized by geography down to the county level, making efficient work of the type of material required to meet the information needs of those interested in researching place-specific cartographic-related resources. Additionally, this guide will help those interested in not only developing a comprehensive collection in these subject areas, but get an understanding of what materials are being collected and housed in specific map libraries, geospatial centers and their related websites. Of particular value are the sections that offer directories of cartographic and GIS libraries, as well as comprehensive lists of geospatial datasets down to the county level. This volume combines the traditional and historical collections of cartography with the modern applications of GIS-based maps and geospatial datasets."--